Weather flying - Buck, Robert N.; Buck, Robert O. (New York : McGraw-Hill Education, 2013)
"The only resource a pilot needs to understand all types of weather and how to fly in it, with coverage of weather creation along with the philosophy of navigating it--now updated to include new technological devices and changes in weather briefings"-
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Aviation meteorology